Kajian Dharma Wacana Diaspora Hindu-Bali di Jawa Timur - Ni Wayan Sartini (Pusat Kajian Bali Universitas Udayana, 2015)
AbstractThe existence of Balinese diaspora in East Java spreads across the districts and cities. Some developments that occurred when the Balinese formed diaspora in East Java, among others include implementing the model of religious activities to inculcate religious teachings such as dharma wacana. This paper aims to describe the structure, rhetorical pattern and linguistic characteristics of dharma wacana delivered in religious events in East Java, especially in Surabaya and Sidoarjo. The analysis suggested that the structure of dharma wacana of Balinese diaspora community consisted of an disclosure, content, and closure. The pattern also indicated that the preacher of dharma wacana had taken a variety of ways and measures for each section and had different communicative purposes as well as used different rhetorical functions. This analysis also suggested that there were some repetitions in pattern and measure such as the repetition of the proposition, quotations, arguments, and solicitation. Another rhetorical characteristic of the text of dharma wacana found in this study was that the preacher relied on references (citations) in the holy verses to justify the importance of the topic of dharma wacana. Linguistic characteristics of dharma wacana includes vocabulary of religious genre and code-mixing between subtle Bali language and Bahasa.